2017
DOI: 10.1007/s00125-017-4285-4
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the regulation of insulin transport across the brain endothelial cell

Abstract: Aims/hypothesis For circulating insulin to act on the brain it must cross the blood–brain barrier (BBB). Remarkably little is known about how circulating insulin crosses the BBB’s highly restrictive brain endothelial cells (BECs). Therefore, we examined potential mechanisms regulating BEC insulin uptake, signalling and degradation during BEC transcytosis, and how transport is affected by a high-fat diet (HFD) and by astrocyte activity. Methods 125I-TyrA14-insulin uptake and transcytosis, and the effects of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 52 publications
4
85
1
1
Order By: Relevance
“…Besides experimental models, in humans, intranasal insulin has been shown to improve memory functions in healthy subjects [61, 62], with no effect on word recall and non-declarative memory but rather on declarative, hippocampus-dependent memory contents [62, 63]. Conversely, both type 1 and type 2 diabetic patients have been shown to exhibit cognitive impairments and an increased risk of Alzheimer disease (AD) [64] consistent with the above-mentioned idea that unfavourable metabolic conditions reduce insulin transport into the brain [9]. Considering the presumable role of insulin regarding brain glucose uptake, this also fits with the reduced brain glucose uptake associated with dementia [65].…”
Section: Central Insulin Signalling: Impact On Cognition and Metabolismsupporting
confidence: 52%
See 1 more Smart Citation
“…Besides experimental models, in humans, intranasal insulin has been shown to improve memory functions in healthy subjects [61, 62], with no effect on word recall and non-declarative memory but rather on declarative, hippocampus-dependent memory contents [62, 63]. Conversely, both type 1 and type 2 diabetic patients have been shown to exhibit cognitive impairments and an increased risk of Alzheimer disease (AD) [64] consistent with the above-mentioned idea that unfavourable metabolic conditions reduce insulin transport into the brain [9]. Considering the presumable role of insulin regarding brain glucose uptake, this also fits with the reduced brain glucose uptake associated with dementia [65].…”
Section: Central Insulin Signalling: Impact On Cognition and Metabolismsupporting
confidence: 52%
“…Insulin transport requires binding to the insulin receptor (IR) and transcytosis of the IR insulin complex through brain endothelial cells. Interestingly, this transport can be modulated, for instance by high-fat diet, astrocyte stimulation, or nitric oxide inhibition [9]. …”
Section: Central Insulin Signalling: Impact On Cognition and Metabolismmentioning
confidence: 99%
“…Using combined IR immunogold labeling and electron microscopy we localized these receptors in astrocytic end-feet ( Figure 1A,B). This anatomical location, in close proximity to endothelial cells, together with the expression of IR in the latter type of cells ( Figure 1B), or as an yet uncharacterized transporter (Rhea et al, 2018), would allow the passage of circulating insulin into astrocytes by transcytosis through endothelial cells (Gray et al, 2017).…”
Section: Irs Are Present In Astroglial End-feetmentioning
confidence: 93%
“…Indeed, there are insulin receptors (IR) in the cells forming the BBBs; that is, epithelial cells at the choroid plexus (Baskin et al, 1986), brain capillary endothelial cells (Frank et al, 1986) that transcytose insulin (King and Johnson, 1985), and astrocytes (Baron- Van et al, 1991). Accordingly, previous observations indicated that insulin from the circulation enters the brain through a transport mechanism involving its receptor in brain endothelial cells forming the BBB (Gray et al, 2017), although more recent observations indicate that the process may be IR independent (Hersom et al, 2018;Rhea et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that small amounts of insulin may be synthesized locally in the brain, however, the physiologic consequence of this remains unclear (Devaskar et al, 1994;Devaskar, Singh, Carnaghi, Rajakumar, & Giddings, 1993). The kinetics of peripheral insulin activating brain insulin signaling appear to be dependent on endothelial IRs, which serve to traffic insulin into the local brain tissue (Gray, Aylor, & Barrett, 2017;Konishi et al, 2017). In addition to the IR, the brain also contains abundant levels of the closely related IGF-1 receptor (IGF1R), as well as its primary ligand, insulin-like growth factor 1 (IGF-1) (Bach, Shen-Orr, Lowe, Roberts, & LeRoith, 1991;Fernandez & Torres-Aleman, 2012).…”
Section: Brain Insulin Receptor and Insulin Resistance In Diabetes mentioning
confidence: 99%